2012
DOI: 10.1002/ijc.27908
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma risk in livestock farmers: Results of the Epilymph study

Abstract: We explored the risk of lymphoma and its most prevalent subtypes associated with occupational contact with livestock, and whether risk was modified by age at first contact, in 2,348 incident lymphoma cases and 2,462 controls who participated in the EPILYMPH case-control study. A detailed occupational history was collected in cases and controls, including working in a livestock farm, species of livestock, its approximate number and circumstances of contact. For each disease outcome, and each type of livestock, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…We confirmed prior findings by InterLymph and others with additional cases and controls for a number of exposures. Specifically, we confirmed the previously reported strong increased risk with family history of hematological cancer (10-12), the increased risk with height (18,19), the increased risk with farming exposures (20)(21)(22)(23)(24), and the protective effect of UV radiation on CLL/SLL risk (25,26). Although we report a significant increased risk with hepatitis C virus herein, we had no additional new data beyond that reported in an earlier InterLymph pooled analysis (27).…”
Section: Discussionsupporting
confidence: 88%
“…We confirmed prior findings by InterLymph and others with additional cases and controls for a number of exposures. Specifically, we confirmed the previously reported strong increased risk with family history of hematological cancer (10-12), the increased risk with height (18,19), the increased risk with farming exposures (20)(21)(22)(23)(24), and the protective effect of UV radiation on CLL/SLL risk (25,26). Although we report a significant increased risk with hepatitis C virus herein, we had no additional new data beyond that reported in an earlier InterLymph pooled analysis (27).…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis (1) that included these (9, 10) and other studies reported that glyphosate exposure was significantly associated with NHL overall (meta risk ratio (mRR) 1.5, 95% CI 1.1-2.0, N=6 papers). The risk of B-cell lymphoma was mRR 2.0, 95% CI 1.1-3.6 (11,12).…”
mentioning
confidence: 97%
“…For example, only three studies (2,9,12) have reported on exposure metrics other than ever or never use. In addition, only three studies have reported any information on risk by NHL sub-type (11,12,18) which have different etiologies (19). Other limitations of previous studies include lack of adjustment for other pesticides.…”
mentioning
confidence: 99%
“…46 To our knowledge, there is no study showing that farmers' children have an increased risk of cancer. 47 Our data suggest that not only immunologic danger signals derived from microbes but also non-microbial-associated molecular patterns can be protective environmental exposures. Linear and logistic (*) regression for the association between immunologic markers (target variable) and exposure variables is shown.…”
Section: Discussionmentioning
confidence: 72%